Diversity of Herpetofauna in Cukunyinyi Mangrove Ecotourism Area, Pesawaran, Lampung - Hasibuan, Mhd Muhajir; Sari, Nurika Arum; Dwiputra, Mohammad Ashari; Permana, Rizki Dimas; Rianingsih, Firma; Adirama, Alfian Zamzami; Witjaya, Oka Rani; Zamili, Abdi Oktarian; Nainggolan, Paolo M.; Aryawan, Adi; Purnomo, Ajis; Sudarsono, Bambang; Hamdani, Hamdani; Aini, Yusratul (Wana Lestari, 2023)
Mangrove are important coastal ecosystems that provide a variety of ecosystem services and ecological functions. These ecosystem services include natural barriers that protect coastal areas from cyclones, tsunamis, and erosion. Habitats for breeding, foraging, and nursery for various species of aquatic and tereterial species. The benefits provided by mangrove are contrast to the rate of degradation. Various parties have a responsibility to contribute to efforts to maintain a sustainable environment. Biodiversity has been globally recognised as one of the determining factors for the sustainability of an ecosystem. The study aims to assess the diversity of herpetofauna species in the Cukunyinyi Mangrove ecotourism area as an instrument of environmental monitoring. The method in this study was the Visual Encounter Survey (VES). The diversity of herpetofauna (H') observed in the area was 1.06 inside the Ecotourism Area and 0.56 outside the ecotourism area. The indices of species richness (Dmg) in each area were 1.24 and 0.72. The two regions have evenly distributed with an evenness value of more than 80%. No species protected under national regulation, two species whose trade was restricted internationally and included in the CITES Appendix II.